A hybrid planar inverted-F spiral antenna for in-body wireless area networks - H. V. Abrahamyan (ՀՀ ԳԱԱ հրատ.)
Nowadays, in hyperthermia and biotelemetry, antennas implanted in a human are widely used. Ներկայումս հեռաբժշկական համակարգերում լայնորեն կիրառվում են մարդու օրգանիզմում տեղադրվող իմպլանտային սարքավորումները: В настоящее время импланты широко используются в гипертермии и биотелеметрии.
Keywords: Electrical engineering; Electronics; Nuclear engineering; Technology